2024
DOI: 10.1186/s41043-023-00493-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tobacco smoking and hematological indices among Sudanese smokers

Izzut Awad Ahmed,
Mahmood Abdalmonem Mohammed,
Hussam Mohammed Hassan
et al.

Abstract: Background Tobacco Smoking is one of the leading causes of preventable morbidity and mortality in the world. It is well documented that tobacco smoking is risk factor for many diseases like: cancers, chronic respiratory and cardiovascular diseases, and the effects of tobacco smoking on hematological indices gets a little attention: the data is mostly inconsistent regarding the differential of WBCs, a conflicting studies described the effect of smoking on hemoglobin descriptive parameters and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…This study corroborates our data in a specific aspect, as no association was found between tobacco consumption and Hb and RBC levels. However, Ahmed et al (2024) [ 118 ] presented different results from the previous study. Aiming at evaluating the relationship between tobacco smoking and haematological parameters among 120 Sudanese healthy smokers, it revealed that smokers had a significantly higher RBC count of 5.37 ± 0.42 (×1012/L) and Hb levels of 16.17 ± 1.58 (10 12 /L).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This study corroborates our data in a specific aspect, as no association was found between tobacco consumption and Hb and RBC levels. However, Ahmed et al (2024) [ 118 ] presented different results from the previous study. Aiming at evaluating the relationship between tobacco smoking and haematological parameters among 120 Sudanese healthy smokers, it revealed that smokers had a significantly higher RBC count of 5.37 ± 0.42 (×1012/L) and Hb levels of 16.17 ± 1.58 (10 12 /L).…”
Section: Discussionmentioning
confidence: 75%
“…The production of this new protein impairs red blood cells from functioning correctly, making it difficult for them to transport oxygen. In response to this situation, the body compensates for the lack of oxygen by entering a state of hypoxia, leading to a chemical response by the brain to stimulate red blood cell production, thereby increasing Hb and HCT levels [ 117 , 118 ]. Aldosari et al (2020) presented similar results, finding that Hb and RBC levels hardly differed between the two groups [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…Factors, including ethnicity, smoking status, and altitude, can all have an impact on variations in red blood cell (RBC) counts [ 11 , 12 ]. People who live at high elevations, for instance, might have increased RBC counts because of the body’s adaptation to low oxygen levels [ 12 ].…”
Section: Introductionmentioning
confidence: 99%